Translation, adaptation, and validation of the Care Coordination Instrument for cancer patients - Anne Werner; Anke Steckelberg; Alexandra Strobel; Andreas Wienke; Heike Schmidt; Dirk Vordermark; Patrick Michl; C. Benedikt Westphalen; Julia Lühnen (BMC Health Services Research)
Abstract Background Cancer requires interdisciplinary intersectoral care. The Care Coordination Instrument (CCI) captures patients’ perspectives on cancer care coordination. We aimed to translate, adapt, and validate the CCI for Germany (CCI German version). Methods The original English version contains 29 items in three domains, measured on a 4-point Likert scale (strongly disagree to strongly agree). Validation was conducted in three phases (mixed methods): (I) translation; (II) adaptation: pilot testing and revision in an iterative process using semi-structured, cognitive interviews with patients and professionals (physicians specializing in cancer), with interviews transcribed and qualitatively analyzed by inductive coding; and (III) validation: quantitative validation performed online (LimeSurvey), of at least 80 German patients, each with common cancer (breast, prostate) and rare cancer (different entities), with examination of factor structure (factor analysis) and determination of internal consistency (Cronbach's α) as well as potential influencing factors such as gender, education, or migration background (multivariable regression). Results Six patients and six professionals tested the translated instrument for comprehensibility, readability, and acceptability. Two items were consistently problematic for interviewees. A 31-item version (29 items + 2 alternative items) was validated in 192 patients. The alternative items had a higher variance in response behavior and were better understood; therefore, they replaced the two problematic items. However, the three original domains could not be confirmed statistically. Exploratively, a two-factorial structure (with cross-loadings) emerged, which can be interpreted as “communication/information” (16 items) and “need-based navigation” (17 items). Overall, the instrument had a high internal consistency (total score α = 0.931, M = 47.16, SD = 14.25; communication/information α = 0.924, M = 30.14, SD = 8.93; need-based navigation α = 0.868, M = 23.99, SD = 8.37). Significant factors on the care coordination score are treatment location (hospital vs. private practice oncologist M = -9.83 score points, p = 0.011) and gender (women vs. men M = 8.92 score points, p = 0.002). Conclusion The CCI German version is a valid instrument for measuring patients’ perceptions of cancer care coordination. Both domains reflect important aspects of care. The sensitivity of the CCI should be examined in future studies involving different cancer entities.